The semiotic theory of "Grimas" between the crisis of the term and the problem of translation - جريوي, آسيا (مجلة المخبر أبحاث في اللغة والأدب الجزائري; No 7 (2019): جامعة محمد خيضر بسكرة مجلة: '' المخبر أبحاث في اللغة والأدب الجزائري'' قسم الآداب واللغة العربية - جامعة بسكرة ، الجزائر, 2022)
The semiotic researcher discovers during his research in the folds of the semiotic theory of "Greimas", the reference tributaries on which the theory was based to elucidate the concepts and procedural tools from the stage of gains (semiotics of action) to the stage of projects (semiotics of passions), and in this process the researcher objects to the problem of assimilating the term Western and translating it from a foreign language into Arabic. Seeking to find the meaning close to it in the Arabic language. Therefore, the researcher's guide to entering the world of semiotic theory is to understand the term semiotic, as it is a fundamental issue before the Arab critic and researcher in his quest to know its meaning in the semiotic field from theory to application. Keywords : Term, semiotics, translation, meaning, semantics.